Pengaruh Model Pembelajaran Kooperatif Tipe STAD Berbantuan Media Poster Terhadap Hasil Belajar Peserta Didik - Kusumawardani, Normasintasari; Siswanto, Joko; Purnamasari, Veryliana (Jurnal Ilmiah Sekolah Dasar, 2018)
This study aims to find out how much influence the cooperative learning model of the poster-assisted STAD type media on the learning outcomes of fifth grade students of SD Negeri Penanggulan Kendal, knowing how much influence the poster-assisted STAD cooperative learning model on the learning outcomes of grade V students of SD Negeri Penanggulan Kendal. Design of the Experimental research method. Design of Intact-Group Comparison. The results showed an increase in student learning outcomes that can be seen based on the results of the pretest and posttest, controls and experiments that have been done.. It was proven in testing the hypothesis, which states that the value of  count smaller than  at value (1.74 ˂ 4.28) which means H0 is accepted and Ha is rejected. The calculation shows that there are differences in student learning outcomes after using poster media on the STAD type cooperative model in the teaching and learning activities that have been carried out. So it can be concluded that learning using the poster media on the STAD type cooperative model is effective against students' mathematics learning outcomes.